2002
DOI: 10.1046/j.1439-0434.2002.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Trichoderma harzianum and T. atroviride to Control Botryosphaeria berengeriana f. sp. piricola, the Cause of Apple Ring Rot

Abstract: Trichoderma harzianum T88 and T. atroviride T95 were tested for their efficacy in controlling apple ring rot (caused by Botryosphaeria berengeriana f. sp. piricola) in vitro and in the field. Isolates of T88 and T95 produced both volatile and non‐volatile antibiotics that suppressed mycelial growth of the pathogen. Light and scanning electron microscopy showed that mycoparasitism by Trichoderma spp. of B. berengeriana f. sp. piricola resulted in penetration and disruption of hyphal cells, and thinning of cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…These results are in agreement with the findings of Adriana and Sergio (2001), Krupke et al (2003), Kexiang et al (2002) and Shafiquzzaman et al (2009).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the findings of Adriana and Sergio (2001), Krupke et al (2003), Kexiang et al (2002) and Shafiquzzaman et al (2009).…”
Section: Resultssupporting
confidence: 93%
“…(62.50%). The inhibition of the radial growth of the test fungi due to non-volatile metabolites, may be attributed to the production of antibiotic substances in the culture filtrates and impoverishment of nutrient (Kexiang et al 2002, Howell 2003, Wool and Larito 2007. It has also been reported that the antibiotic production varies depending on the comparing organisms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ultrastructural studies have been widely used to observe the mycosparasitism of Trichoderma spp. on coiling and penetration of hyphae in plant pathogens in the Ascomycete and Basidiomycete, but few studies have investigated this approach for Oomycetes (Elad, 1988;Benhamou and Chet, 1996;Gupta et al, 1999;Kexiang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tronsmo and Dennis (1977) were able to protect strawberry fruits against storage rot caused by Botrytis cinerea and Mucor mucedo by spraying strawberry plants in the field during early flowering, with aqueous suspensions of conidia of T. viride and T. polysporum. Kesiang et al (2002) found the efficacy of the control of apple ring rot caused by Botryosphaeria beregeriana f. sp. pericola with Trichoderma to be similar to that of a chemical control.…”
Section: Introductionmentioning
confidence: 99%